EGFR and KRAS mutations detection on lung cancer liquid-based cytology: a pilot study. Issue 1 (22nd September 2011) - Malapelle, Umberto; de Rosa, Nicla; Rocco, Danilo; Bellevicine, Claudio; Crispino, Carlo; Illiano, Alfonso; Piantedosi, Franco Vito; Nappi, Oscar; Troncone, Giancarlo
Abstract : In advanced non-small-cell lung carcinomas epidermal growth factor receptor (EGFR) and KRAS testing is often performed on cytology. Liquid-based cytology (LBC), which eliminates the need for slide preparation by clinicians, may be very useful. In 42 LBC DNA was extracted twice. One sample was obtained directly from CytoLyt solution, whereas the other DNA sample was derived after smear preparation and laser capture microdissection (LCM) of Papanicolaou-stained cells. EGFR and KRAS mutational analyses were performed by direct sequencing. On CytoLyt-derived DNA four EGFR (9%) and five KRAS (12%) gene mutations were found. When direct sequencing was performed after LCM, the rate of cases that displayed either EGFR or KRAS mutations increased from 21% to 40%. Although time-consuming, LCM makes direct sequencing highly sensitive even on LBC preparations containing only a few cells.